Transcriptomic profiling and longitudinal study reveal the relationship of anti-MDA5 titer and type I IFN signature in MDA5+ dermatomyositis - Wang, Yan; Jia, Hongxia; Li, Wei; Liu, Hongping; Tu, Meng; Li, Jing; Cheng, Jiuling; Zhang, Guojun (Frontiers in Immunology, 2023)
Objective This study aimed to investigate the relationship between anti-MDA5 titer and type I IFN signature in patients with MDA5+ DM. Methods We explored the transcriptome profiling of PBMCs in MDA5+ DM patients with high-titer of antibody at disease onset or relapse and normal low-titer after treatment and healthy donors. Subsequently, we revealed the dynamic relationship between serum type I IFN scores and antibody titers. Result Differentially expressed genes in MDA5+ DM patients were enriched for related pathways and biological functions linked to viruses and cytokines compared to healthy donors. Similar differences remained pooled between the high-titer and low-titer group, and type I-specific interferon response genes showed upregulation in high-titer group. Significant correlations were found between anti-MDA5 titers and type I IFN scores (r = 0.50, P< 0.001). Contemporaneous anti-MDA5 titers revealed to be significantly higher in the group with ultra-high type I IFN scores (vs. high group, P = 0.027; vs. low group, P< 0.001). Longitudinal assessment of type I IFN scores and anti-MDA5 titers, including pre- and post-treatment changes at initial diagnosis and dynamic changes during treatment, presented an asynchrony between the two parameters in response to treatment. Conclusion Anti-MDA5 antibody titers correlated with type I IFN signature in patients with MDA5+ DM and they both changed dynamically but not synchronously over the course of treatment.